The Political Economy of Digital Inequality and Education; Rights in Kenya and Indonesia - Alwy Ahmed Mohamed; Mowafg Masuwd; Mahmudulhassan Mahmudulhassan; Usman Aliyu Yunusa (International Journal of Social and Political Sciences, 2026)
This study examines the impact of digital inequality on the right to higher education in Kenya and Indonesia through a comparative political economy perspective. Digital transformation has expanded opportunities for learning, but it has also exposed unequal access to technology, internet connectivity, digital devices, and digital literacy among students and institutions. Using a qualitative comparative approach, this study relies on secondary data, policy documents, institutional reports, and relevant academic literature to analyze how structural disparities shape access to digital higher education in both countries. The findings show that Indonesia has made broader progress in expanding digital infrastructure and online learning systems, yet it continues to face significant regional gaps, particularly between urban and remote areas. Kenya, by contrast, demonstrates stronger digital innovation and a dynamic technology ecosystem, but affordability, unstable connectivity, and uneven institutional capacity remain major barriers. In both contexts, digital inequality is not merely a technical problem, but a structural issue shaped by socioeconomic status, geography, market access, and policy implementation. These inequalities limit the realization of the right to higher education and risk reproducing existing social exclusion. The novelty of this study lies in integrating rights-based analysis with political economy to compare digital inequality across two Global South contexts. The study recommends stronger regulation, affordable connectivity, inclusive digital infrastructure, and equity-oriented higher education policies.